Value Stream Mapping and Flexible Manufacturing at Crown Holdings INC - Fraser, Dougal (2005)
This MBA dissertation is the result of investigations conducted into flexible manufacturing approaches for Crown Holdings Inc. The objective of the dissertation was to define manufacturing flexibility and its associated paradigms in relation to Crown processes by piloting value stream mapping techniques within the European Aerosols Division. A secondary objective was subsequently established to produce a process or learning to see mapping model and evaluate its effectiveness as a future tool for Crown to use.